Distribution characteristics and risks assessment of brominated flame retardants in surface soil from both a legacy and a new e-waste dismantling site. (1st November 2022) - Ling, Siyuan; Lu, Cong; Fu, Mengru; Zhou, Shanqi; Qiao, Zhihua; Peng, Cheng; Zhang, Wei; Hu, Shuangqing; Lin, Kuangfei; Zhou, Bingsheng
Abstract: Brominated flame retardants (BFRs) are widely used in diverse industries, resulting in extensive environmental contamination. Although many legacy BFRs have been banned and replaced with novel brominated flame retardants (NBFRs), these NBFRs have also been found to exhibit toxicity and persistence. In this study, 55 soil samples were collected from areas surrounding an abandoned (FJ) and a newly built (TZ) e-waste dismantling zone which represent the traditional and modern e-waste dismantling practice in China, respectively, to examine and compare the occurrence of BFRs and their potential ecological and health risks. The concentrations of novel brominated flame retardants (NBFRs) ranged from 10.0 to 2, 390 ng/g dw, and those of polybrominated diphenyl ethers (PBDEs) ranged from 78.0 to 13, 300 ng/g dw. Decabromodiphenyl ethane (DBDPE) to BDE-209 ratios were greater than one in 6.8% and 25% of samples in FJ and TZ, respectively. BFRs concentrations in FJ soils significantly decreased with increasing distance to the center of FJ, indicating that the soil in the FJ region was strongly affected by the e-waste dismantling activities in FJ. For TZ, only DBDPE exhibited similar regulation, indicating that the newly built e-waste dismantling zone has already impacted on the surrounding environment. The Mann–Whitney test showed that the concentrations of most PBDE congeners were higher in FJ ( P < 0.01/0.05) than those in TZ, while there was no significant difference in the concentrations of most NBFRs between FJ and TZ. A low abundance of BDE-209 in soils suggests that its degradation process and DBDPE was the predominant NBFRs in soils from both FJ and TZ. It was found that low-brominated PBDE congeners posed high ecological risks to terrestrial animals, which the ecological risks may increase in the future due to the debromination process of high PBDE congeners. The health hazard of BFRs via soil exposure in FJ was generally higher than in TZ, although both were acceptable. Despite much greater average daily doses for BDE-209 and DBDPE, the oral hazard quotients of BDE-47 and BDE-99 were much higher. Toddlers were found to face a higher health risk due to soil exposure than teenagers and children. The carcinogenic effect of BDE-209 was also acceptable in FJ and TZ. With the continuous operation of the TZ site, the further accumulation of BFRs in soils and health hazard via BFRs exposure are expected, and the results suggest that ongoing monitoring and further research is necessary. We believe that our work could help researchers investigate and reveal the harmful impacts of NBFRs and PBDEs. Graphical abstract: Image 1 Highlights: E-waste dismantling activities in Luqiao have severely polluted the soils. BDE-28, BDE-47 and BDE-99&-100 have posed high ecological risks. The average daily dose via soil exposure of DBDPE and BDE-209 were comparable in TZ. The non-carcinogenic and carcinogenic health risks were higher in FJ and acceptable in both zones.